‘Stilfarbe’ en ‘Farbkunst’. De (her)ontdekking van negentiende- en vroegtwintigste-eeuwse kleurtheorie in relatie tot kunstnijverheid, schilderkunst en architectuur (Bulletin KNOB, 2017)
One hundred years after its emergence, the Amsterdam School still manages to fascinate people with its whimsical forms and bright colours. Although the frame of reference for the forms is known, there has been less interest in investigating the use of colour. The (Dutch) catalogue to the ‘Living in the Amsterdam School’ exhibition touched on the topic visually, noting similarities with German expressionism and the art of Wassily Kandinsky. This article addresses the affinity between the Amsterdam School and painting from the perspective of the investigation of style and ornament from the second half of the nineteenth century. The accompanying linkage of developments in architecture, applied art and painting is discussed in terms of colour theory.Underpinning this are the book Stilarchitektur und Baukunst (Style-architecture and Building-art, 1901) by Hermann Muthesius, from which the title of this article is borrowed, Wassily Kandinsky’s Über das Geistige in der Kunst (Concerning the Spiritual in Art, 1912), and Josef August Lux’s ‘Die Erneuerung der Ornamentik’ (The Revival of Ornament,1908).When developments in applied art, painting and architecture are looked at conjointly, it becomes evident that the Amsterdam School was not an isolated phenomenon but one step in a development that originated in the nineteenth century. Colour theory is part of this development and key to the astonishingly bright but harmonious use of colour in the Amsterdam School. The lead-in was Owen Jones’s celebrated Grammar of Ornament (1856), which referred to new colour theories. From the emergence of the new approach to applied art around 1850, ornament changed in the space of sixty-odd years from impressionistic stylization of natural forms and colours into the psychological linking of line, form and colour in expression. While the use of colour was generally harmonious, the colour palette changed in line with the abstraction. At the end of the nineteenth century, neo-impressionism accelerated the development of a new ornamentation. Artist-architects like Henry van de Velde, who had started out as painters, were the prime movers, including in the field of colour. For abstract (line) ornaments, ‘pure colours’ were used, including secondary colours. According to the principles of neo-impressionism, which were based chiefly on the colour theory and ‘simultaneous contrast’ of Michel-Eugène Chevreul, these colours were not to be mixed. The main thing was the psychological experience in the association of line, form and colour that is characteristic of expressionism, as also described by Johannes Itten in his colour theory. With the transition from Gesamtkunstwerk to Gemeenschapskunst the stylized natural ornaments changed, under the influence of theosophy, into rhythmical geometric patterns and subjective colour experience became objectively verifiable. Goethe’s ‘sensuous-moral effect of colour’, Rudolf Steiner’s ‘Das Wesen der Farbe’ (Nature of Colour), as well as the scientifically underpinned colour harmonies in standardized colours according to Ostwald, can be seen as attempts to capture colour objectively.The visual similarity with expressionism can be substantiated. Kandinsky’s Über das Geistige in der Kunst – often regarded as a paraphrase of Goethe’s 1810 colour theory – is helpful in understanding the views on form and colour in the Amsterdam School. Regarded in this light, expressionism is not so much synonymous with bright colours as with the psychological combination of form and colour as an expression in an inner impression. The Amsterdam School pursued the expressionistic combination of form and colour in an objectified manner, in what one could call ‘objective expressionism’, where the colours in the rhythmical geometric patterns correspond to the colours of the neo-impressionistic painter’s palette.